Orientation of ambiguous image sequences with similar and repeated structures - G. Perda; L. Morelli; F. Remondino (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Image orientation, nowadays called Structure from Motion (SfM), is still an open research topic in particular in case of scenes featuring visual aliasing, or doppelgangers. Indeed, visually similar but distinct elements of the scene can cause incorrect matches, not detected by geometric or learning-based outliers removal methods, leading to misplaced camera poses and wrong 3D reconstructions. The paper reviews various state-of-the-art approaches to orient ambiguous image sequences and determination correct camera orientation parameters. We also present an in-house graph-based approach to reliably and precisely orient sets of images with doppelgangers. Different experiments on common ambiguous datasets are reported and commented.